Consumer food safety education for the domestic environment: A systematic review - Milton, A.; Mullan, Barbara (Emerald Group Publishing Limited, 2010)
Purpose – Despite the recognised importance of food safety, a large number of consumers do not practice adequate food safety in the home. Many studies have recommended that education is a key step in preventing food-borne illness in the domestic environment. However, few educational or psychosocial interventions have been designed and implemented to improve food safety knowledge, attitudes and behaviours. Even fewer of these studies have been subject to rigorous appraisal. The purpose of this paper is to conduct a systematic review of studies that described and evaluated a food safety intervention in a non-clinical adult sample. Design/methodology/approach – A total of ten studies met the criteria for inclusion in the systematic review. Outcomes of interest included food safety behaviour, behavioural intention, attitudes, knowledge, microbial transfer and the use of social cognition models. Findings – The evidence regarding the effectiveness of the reviewed interventions on these food safety outcomes was somewhat positive; however, many gaps remained. For example, of the five self-report behaviour change studies, all reported some significant improvement post-intervention. However, the percentage of specific behaviours that significantly changed within each study varied between 0.04 and 100 per cent. There were methodological flaws in many of the studies which complicated the interpretation of these results and indicate a need for more research.Research limitations/implications – Future research should include better defined outcomes, longer follow-up, more rigorous reporting of results and intervention design, the use of randomised controlled trial protocols and utilising health models to have a greater theoretical underpinning to the studies. Originality/value – This paper is the first systematic review examining the effect of psychosocial food safety interventions on behaviour, attitudes and knowledge.